Upaya Peningkatan Mobilitas Fisik Pada Pasien Stroke Nonhemoragik - Restu Nurani, Hanifah; , Enita Dewi, S.Kep., Ns (2017)
background: Stroke is a problem for developing countries. In the United States, stroke is the third causing death after heart disease and cancer. Indonesian datas show thatthe incidence of stroke are 234 of 100,000 people, the national show that the main causing death in all ages is stroke (15.4%). The frequents problem accured to stroke patient is paralized. For increasing muscle's power, we nedd to do mibilization and afrercare training, in oeder to repair neurological functions and to prevent contractures by doing physical theraphies and other techniques. Objective: To describe intervention to increase physical mobility in stroke patients nonhemoragik Methods: The descriptive method with case study approach. The collection of data by observation, physical examination, medical records, interviews, documentary studies of journals and books. Results: There is not improvement of the physical mobilization on the patient yet after the action. Conclusion: The action Range Of Motion (ROM) and Interpretation reposition effectively improve physical mobilityA Advice: action ROM and Interpretation reposition can be as inputs in independent nursing action to deal with improve physical mobility Keywords: Stroke, physical mobility, range of motion, control bearing.